Replication in village-level studies - Hockings, Paul (1999)
Village studies have long been done in India, either by British government personnel or by academics, particularly economic historians and social anthropologists. Some are highly quantitative, others rely more heavily on verbal description. In a relatively few cases the same village or set of villages has been restudied, and in one extreme case over a span of nearly 150 years. After briefly surveying some of the most useful of these longitudinal studies, the author describes in some detail his own 27-year study of a set of four Badaga villages in the Nilgiri Hills of Tamil Nadu. All were clustered together, but represented different phratries and social strata in this traditionally peasant millet-farming community of 1,60,000 people. Some conclusions are drawn about the nature of modernisation here, and evidence is produced to suggest that the process - which involves universal schooling, reduced fertility rates, television viewing, and changing attitudes towards the family itself - is having a levelling effect on these particular villages, with the one that would traditionally have been lowest in status now showing many progressive features. - Reproduced
Keywords: Rural areas; Rural development